Empowering Pronunciation Learning through Google Translate TTS: Insights from SMA 4 Jember Students - Subhanadif Akmal Bariq; Muhlisin Rasuki; Indri Astutik (Institut Agama Islam Tarbiyatut Tholabah, 2026)
Abstract This study investigates the effectiveness of Google Translate's Text-to-Speech (TTS) feature in improving English pronunciation among vocational high school students. The research employs a quantitative approach, focusing on pre-test and post-test assessments to measure the impact of the TTS feature on students' pronunciation skills. The study begins by outlining the background and significance of pronunciation in English language learning, emphasizing the challenges students face in achieving accurate pronunciation. It explores the potential of TTS technology as a digital learning tool that provides students with authentic pronunciation models. The research aims to determine whether exposure to TTS-generated speech enhances students' ability to pronounce words correctly and fluently. Data collection involves a controlled experiment where students undergo a pre-test, engage with TTS as a pronunciation training tool, and subsequently take a post-test. The results are analyzed statistically to identify significant improvements in pronunciation accuracy. Findings suggest that the integration of TTS technology in language learning positively influences students’ pronunciation performance, making it a viable supplement to traditional teaching methods. The study concludes by recommending the adoption of TTS technology in English language instruction, highlighting its advantages in providing consistent pronunciation models and facilitating independent practice. Future research directions include exploring the long-term effects of TTS exposure on pronunciation retention and comparing TTS with other pronunciation enhancement methods.